Oxygen-dislocation interaction in titanium from first principles. (15th March 2019) - Chaari, Nermine; Rodney, David; Clouet, Emmanuel
Abstract: The interaction between screw dislocations and oxygen interstitial atoms is studied with ab initio calculations in hexagonal close-packed titanium. Our calculations evidence a strong repulsion when the solute atoms are located in the dislocation glide plane, leading to spontaneous cross-slip, which allows the dislocation to bypass the atomic obstacle. This avoidance process explains several experimental observations in titanium in presence of oxygen: (1) a larger lattice friction against screw dislocation motion, (2) a reduction of the dislocation glide distance in prismatic planes and (3) an enhancement of cross-slip in pyramidal planes. Graphical Abstract: